x - 2x

Let x = 1:

1 - (2 x 1)

1 - 2 = -1

therefore

(1)x - 2x = -(1)x

really, the inputed "1"s are unnecessary, as it means the same thing, but I may as well have them there.

x - 2x

Let x = 1:

1 - (2 x 1)

1 - 2 = -1

therefore

(1)x - 2x = -(1)x

really, the inputed "1"s are unnecessary, as it means the same thing, but I may as well have them there.

What Is X Minus 2x?

x-2x=

1x-2x=

-1x=

-x

X-2X=

1X-2X=

-1X=

-X

X-2x can't be simplified

X ≠ x

(x) - (2x)

= x(1 - 2)

= x(-1)

** = -x**

= x(1 - 2)

= x(-1)

Didn't find the answer you were looking for?